PENERAPAN METODE KRITERIA OPTIMUM DAN FAKTOR SKALA PADA OPTIMASI STRUKTUR RANGKA PENERAPAN METODA KRITERIA OPTIMUM DAN DENGAN KENDALA PERPINDAHAN TUNGGAL - Kuntjoro, Wahyu (Mesin, 1999)
An optimization process could be performed through a priori speciï¬cation of a set of conditions to be satisfed by the optimum design. By manipulating the optimality criteria, simple redesign equations can be derived. This research looks at mathematical criteria obtained from diferentiation of Lagrangian with respect to the design variabels. In deriving the optimality criterion and developing the algorithm, ï¬ll use is made of the knowledge of the behaviour of the constraint imposed on the structure. Scale factor is applied to a design which meets the optimality criteria. âA computer program has been developed and applied to a frame structure. The design output is compared to the optirnumgdesign produced by NASIRAN Sol-200 optimization package.